PHILOSOPHICAL PERSPECTIVES IN INTEGRATING ELT TO BIOLOGICAL EDUCATION AND LITERATURE STUDY: AN INTERDISCIPLINARY APPROACH - Indriyani, Dian; Revisika, Revisika (Publikasi dan UKI Press UKI Toraja., 2025)
Philosophy and education have a close relationship. The relationship between the two is inseparable, so sometimes the philosophy of education is called educational theory, and vice versa. The purpose of this article is to analyze how philosophy is viewed in educational practice. The method used is the library study method (library reserch), which is a research activity carried out by collecting data and information with the help of various kinds of materials in libraries and other online media such as reference books, similar previous research results, articles, notes, and various journals related to the problem to be solved. In any science, philosophy is needed because in philosophy we can think deeply about a science, especially in the world of education. The philosophical perspective provides a foundation of thought and conceptual framework for educators in understanding the objectives of the education curriculum, methods and assessments in education. Philosophy can provide various perspectives that can help educators to understand and advance practices in the world of education.